1979
DOI: 10.1136/gut.20.9.797
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in advanced gastric cancer: a controlled, prospective, randomised multi-centre study.

Abstract: SUMMARY Seventy-six patients with advanced gastric adenocarcinoma were studied in a prospective, randomised, controlled trial using vincristine, methotrexate, cyclophosphamide, and 5-fluorouracil in an initiation course and mitomycin-C with 5-fluorouracil as maintenance therapy. Thirty-seven patients were inoperable and 39 had the primary tumour resected with histological evidence of residual disease. Survival in the inoperable group was short and showed no significant difference between treated and control pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Advanced tumours are associated with a poor prognosis, marginally improved by chemotherapeutic regimens. Any benefit from systemic therapy is usually abrogated by systemic toxicity (Rake et al, 1979;Engstrom et al, 1985;Bleiberg, 1990). For this reason a non-toxic, effective, treatment modality would be of value to improve the outlook for those patients with advanced disease.…”
mentioning
confidence: 99%
“…Advanced tumours are associated with a poor prognosis, marginally improved by chemotherapeutic regimens. Any benefit from systemic therapy is usually abrogated by systemic toxicity (Rake et al, 1979;Engstrom et al, 1985;Bleiberg, 1990). For this reason a non-toxic, effective, treatment modality would be of value to improve the outlook for those patients with advanced disease.…”
mentioning
confidence: 99%
“…However, at least three studies of the decade have not confirmed these results 18,28,33 . With the evolution of both chemotherapy and supportive care, new studies in the 90´s showed clear benefit in favor of palliative chemotherapy.…”
Section: Palliative Chemotherapy Metastatic Gastric Cancer: Clinical mentioning
confidence: 83%
“…No randomised trials have compared single agents with no treatment, but two studies have compared combination treatment containing fluorouracil with no treatment. '6 17 These failed to show that chemotherapy prolonged survival but can be criticised because the prognostic factors favoured the no treatment arms. Randomised trials have thus not proved that single agent or combination chemotherapy prolongs survival in patients with advanced stomach cancer.…”
mentioning
confidence: 99%